2007
DOI: 10.1507/endocrj.k05-112
|View full text |Cite
|
Sign up to set email alerts
|

Influence of L-Thyroxine Administration on Poor-platelet Plasma VEGF Concentrations in Patients with Induced Short-term Hypothyroidism, Monitored for Thyroid Carcinoma

Abstract: Abstract. Angiogenesis is a process of new blood vessel development from pre-existing vasculature. It is a crucial process in normal physiology, as well as in several pathological conditions. The vascular endothelial growth factor (VEGF) represents a family of specific endothelial cell mitogens, involved in normal angiogenesis and in tumour development. The aim of the present study was to estimate the influence of L-thyroxine (L-T 4 ) administration on poorplatelet plasma (P-PP) VEGF concentrations in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Wang et al (18) reported that diiodothyropropionic acid induces formation of new coronary arteries by increasing the protein expression of fibroblast growth factor, vascular endothelial growth factor (VEGF), angiopoietin-1 and endothelium-specific receptor tyrosine kinase 2 in the heart. Dedecjus et al (42) demonstrated that T 4 administration increased plasma VEGF levels. Our results from the angiogenesis-focused array show that VEGF mRNA was not changed by administration of T 3 in AAC heart, and VEGF protein expression level in coronary ECs was not affected by T 3 administration in control mice (control, 1.01 Ϯ 0.12; control ϩ T 3 , 1.01 Ϯ 0.03 arbitrary unit) or AAC mice (AAC, 0.86 Ϯ 0.13; AAC ϩ T 3 , 0.81 Ϯ 0.01 arbitrary unit, determined by Western blot).…”
Section: Discussionmentioning
confidence: 98%
“…Wang et al (18) reported that diiodothyropropionic acid induces formation of new coronary arteries by increasing the protein expression of fibroblast growth factor, vascular endothelial growth factor (VEGF), angiopoietin-1 and endothelium-specific receptor tyrosine kinase 2 in the heart. Dedecjus et al (42) demonstrated that T 4 administration increased plasma VEGF levels. Our results from the angiogenesis-focused array show that VEGF mRNA was not changed by administration of T 3 in AAC heart, and VEGF protein expression level in coronary ECs was not affected by T 3 administration in control mice (control, 1.01 Ϯ 0.12; control ϩ T 3 , 1.01 Ϯ 0.03 arbitrary unit) or AAC mice (AAC, 0.86 Ϯ 0.13; AAC ϩ T 3 , 0.81 Ϯ 0.01 arbitrary unit, determined by Western blot).…”
Section: Discussionmentioning
confidence: 98%
“…DITPA administration increased the protein expression of vascular endothelial growth factor (VEGF) 164 , VEGF 188 , basic fibroblast growth factor (bFGF or FGF2), angiopoietin-1 and Tie-2 and bFGF in neovascularisation around infarction areas ). More recently, T 4 treatment restored poor platelet plasma VEGF levels in hypothyroid patients to levels in euthyroid controls, but the blood vessel density was not reported (Dedecjus et al 2007).…”
Section: Introductionmentioning
confidence: 95%
“…In a chick chorioallantoic membrane model, thyroid hormone exhibited FGF-2-dependent proangiogenic effects (Davis et al, 2004). Furthermore, patients who have short-term thyroid hormone deficiency have lower VEGF blood levels that can be reversed by thyroid hormone treatment (Dedecjus et al, 2007).…”
Section: Introductionmentioning
confidence: 99%